1986
DOI: 10.1126/science.3016902
|View full text |Cite
|
Sign up to set email alerts
|

Direct Polyclonal Activation of Human B Lymphocytes by the Acquired Immune Deficiency Syndrome Virus

Abstract: When B lymphocytes from normal human peripheral blood were incubated for 1 hour with the retrovirus that causes the acquired immune deficiency syndrome (AIDS), the B cells showed marked proliferation and differentiation. Proliferative responses to the virus peaked on day 4 and appeared to be independent of accessory cells. This finding was repeated with three separate viral isolates, one of which was from a patient from Zaire. The magnitude of the observed responses was comparable to that seen with standard po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
1
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(136 citation statements)
references
References 19 publications
2
132
1
1
Order By: Relevance
“…Several mechanisms have been suggested for excessive B cell activation in HIV-1 disease, including the direct stimulatory effects of viral proteins on B cells and induction of B cell stimulatory cytokines associated with HIV-1 infection (25). In addition, enhanced T cell help has been implicated in the induction of polyclonal B cell activation (45,46). It has been demonstrated that the envelope glycoproteins induce differentiation of B lymphocytes from normal volunteers into Ig-secreting cells (20,25).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been suggested for excessive B cell activation in HIV-1 disease, including the direct stimulatory effects of viral proteins on B cells and induction of B cell stimulatory cytokines associated with HIV-1 infection (25). In addition, enhanced T cell help has been implicated in the induction of polyclonal B cell activation (45,46). It has been demonstrated that the envelope glycoproteins induce differentiation of B lymphocytes from normal volunteers into Ig-secreting cells (20,25).…”
Section: Discussionmentioning
confidence: 99%
“…4,82 The broad activation of B lymphocytes in HIV infection is wellcharacterized. [3][4][5][7][8][9] This B cell activation, with the expansion of EBV-infected B cell populations, may be the initial steps in B lineage tumorigenesis and may account for the high frequency of oligoclonal lymphoma observed in these patients. 5 Such a broad lymphocyte activation may predispose to the generation of lymphoma even in the absence of EBV infection.…”
Section: Gammopathy and Plasma Cell Tumors In Aidsmentioning
confidence: 99%
“…3,5 B cells exposed to HIV in vitro may proliferate 6 or become activated and begin secreting immunoglobulin. 4,7,8 HIV-infected T cells can induce contact-dependent but antigen-independent polyclonal activation of B cells. 9 Bone marrow biopsy of HIV-infected patients commonly reveals a plasmacytosis, even in the absence of any plasma cell disorder.…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection induces a vigorous immune response with a 10-fold increase in polyclonal immunoglobulin production. Polyclonal B cell activation by HIV may be a direct mitogenic effect or may be antigenspecific (Schnittman et al, 1986). Parasite induced T cell immunosuppression and polyclonal B-cell activation are thus features of both HIV and malaria infection and suggests that HIV infection may be performing an analogous role to holoendemic malaria in the pathogenesis of BL.…”
Section: Burkitt's Lymphomamentioning
confidence: 99%